ANALISIS KESULITAN GURU DALAM MENGIMPLEMENTASIKAN PENILAIAN AUTENTIK KURIKULUM 2013 PADA PEMBELAJARAN TEMATIK DI SEKOLAH DASAR (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Thematic learning in elementary schools is organized in the form of learning that integrates various competencies from various subjects. The purpose of this study was to determine the analysis of teacher difficulties in implementing authentic 2013 curriculum assessments in thematic learning in elementary schools. This study uses a qualitative approach with the method used in this research is descriptive, data collection techniques used are document study, observation, and interviews. The results showed that the authentic assessment at SDN 2 Bandar Agung was implemented quite well by the teachers and was in accordance with the existing aspects of authentic assessment, namely aspects of attitude, aspects of knowledge and aspects of skills. But in applying this assessment model, there are still some teachers who do not understand and experience difficulties in implementing this authentic assessment. There are difficulties faced by teachers at SDN 2 Bandar Agung, namely difficulties in determining assessment criteria, difficulties in giving scores.